Paraneoplastic pemphigus and myasthenia gravis as the first manifestations of a rare case of pancreatic follicular dendritic cell sarcoma: CT findings and review of literature - Lu, Tao (BMC Gastroenterol, 2019)
BACKGROUND: Follicular dendritic cell sarcoma (FDCS) is a rare neoplasm that originates from follicular dendritic cells in lymphoid tissue while paraneoplastic pemphigus (PNP) is an autoimmune blistering disease associated with neoplasms. Pancreatic FDCS associated with PNP and myasthenia gravis (MG) is even rarer and highly malignant. We present the clinical data, pathological materials and computed tomography (CT) features of a rare case of this disease. CASE PRESENTATION: A 49-year-old woman presented with repeated ptosis of both eyelids, oral ulcers and erosions. Her laboratory results showed a slight elevation of CA125 and positivity of some autoimmune antibodies. CT revealed a round solid mass with central necrosis in the pancreatic tail. The solid component of the mass showed slight enhancement and serpentine feeding arteries in the arterial phase, moderate enhancement with a draining vein around the tumor in the portal venous phase and persistent enhancement in the delayed phase. Surgical resection was performed, and the pathological diagnosis was FDCS. However, the patient died of inability to excrete sputum and occlusion of the respiratory tract. CONCLUSIONS: Pancreatic FDCS manifested as PNP and MG is very rare. Its CT features are not specific, and the disease should be differentiated from neuroendocrine tumors, solid pseudopapillary neoplasms and acinar cell carcinoma.